Association between triglyceride-glucose index and risk of colorectal carcinogenesis: a meta-analysis of observational studies - Wang, Lichao; Lin, Yuxuan; Liao, Yonghe; Shen, Jinhai (Frontiers in Oncology, 2025)
BackgroundThe relationship between the triglyceride-glucose (TyG) index and the risk of colorectal carcinogenesis, encompassing both colorectal adenomas and carcinoma, is not yet definitively established. This meta-analysis aims to synthesize available evidence to provide a comprehensive estimate of the association between the TyG index and the likelihood of this disease spectrum.MethodsA systematic search was conducted in PubMed, Embase, and Scopus to identify studies examining the TyG index and colorectal carcinogenesis risk. Meta-analysis was performed to calculate effect sizes (ESs) and their corresponding 95% confidence intervals (CIs) to obtain a summary estimate.ResultsA total of nine observational studies involving 1,056,401 participants were included in the analysis. The meta-analysis revealed that a continuous increase in the TyG index was associated with an elevated risk of colorectal carcinogenesis (ES, 1.19; 95% CI, 1.05-1.34). Similarly, a one-unit increase in the TyG index was linked to an increased risk of colorectal carcinogenesis (ES, 1.24; 95% CI, 1.15-1.32). Additionally, compared to the lowest quartile, the second (ES, 1.07; 95% CI, 1.02-1.13), third (ES, 1.12; 95% CI, 1.06-1.18), and highest quartile (ES, 1.19; 95% CI, 1.13-1.24) of the TyG index exhibited a significantly higher risk of colorectal carcinogenesis.ConclusionThis meta-analysis demonstrates a significant association between the TyG index and colorectal carcinogenesis, suggesting that the TyG index could serve as a convenient and reliable surrogate marker for identifying individuals at risk. These findings may inform screening and prevention strategies targeting the full spectrum of colorectal neoplasia. Standardization of TyG index cutoffs and validation in diverse populations are warranted.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024605775.